Pengaruh Persepsi Manfaat dan Persepsi Kemudahan Penggunaan Terhadap Minat Menggunakan E-Money Berbasis Server - Almira Deana Savitri Almira Deana Savitri; Abdul Muslim Abdul Muslim (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study was conducted with the aim of knowing the effect of perceived benefits and perceived ease of use on interest in using the server-based e-money among OVO users in Bekasi City. The research method used is descriptive quantitative analysis method. Data were collected through questionnaires distributed through social media. This study used unlimited population, namely all users of the OVO application in Bekasi City. The sample consisted of 155 respondents who were selected using a non- probability sampling technique, namely accidental sampling. Data analysis was caried out using multiple linear regression analysis with the help of IBM Statistics version 25 software.The results showed that partially the perceived benefit variable had a positive and significant influence of 41.1% on the interest in using the server- based e-money, and the perceived ease of use variable had a positive and significant effect of 26.5% on the interest in using the server- based e-money. Simultaneously the perception of benefits and perceived ease of use variables has a positive and significant effect of 43.2% on interest in using the server-based e-money, with the remaining 56.8% being the influence of other variables not examined in this study.